Numbers and Narratives — or : When Russell meets Zhu Shijie to discuss Philosophy of Mathematics - Bréard, Andrea (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2022)
Even if no explicit meta-discourse on mathematics is found in pre-modern China outside of mathematical writings, reflections upon objects of mathematical inquiry and the mathematician’s toolbox existed. They are shown to be built into the corpus of Chinese mathematics itself. As illustrated in particular through one specific mathematical domain that evolved from the first to the 19th century, such philosophical reflections are dispersed between texts, paratexts and images, thereby borrowing concepts and iconic images from other Chinese contexts of philosophical nature.